Program pathways for sustainable, nutrition sensitive school meals: An updated framework - Gelli, Aulo; Bliznashka, Lilia (International Food Policy Research Institute, 2024)
Global burden of disease analyses estimate that 20% of deaths are due to unhealthy diets (Afshin et al., 2019). Micronutrient deficiencies impair children’s physical and mental development (Bailey et al., 2015). The prevalence of obesity in children and adolescents increased from less than 1% in 1975 to 6% for girls and 8% for boys in 2016 (NCD Risk Factor Collaboration (NCD-RisC), 2017). The modernization of food systems in low- and middle-income countries (LMIC) has led to rapid shifts to unhealthy diets and reductions in physical activity that have contributed to the global increase in rates of overweight and obesity (Popkin et al., 2020). Moreover, current dietary and population trends will exacerbate risks to people and the planet (Willett et al., 2019). Attention to nutrition during all stages of child and adolescent development is necessary to ensure that children can thrive over the 8,000-day period spanning infancy to adulthood, and to protect investments made earlier in the life cycle (Black et al., 2013). School feeding programs, or school meals, is a widely implemented intervention with documented impacts across social protection, education, health and nutrition (Alderman et al., 2024). Globally, programs reach about 368 million children for a total investment of about $70 billion a year (World Food Programme, 2020).